Zombie lending to U.S. firms - Giovanni Favara; Camelia Minoiu; Ander Pérez (Federal Reserve Bank of Atlanta, 2024)
We show that U.S. banks do not engage in zombie lending to firms of deteriorating profitability, irrespective of capital levels and exposure to such firms. In contrast, unregulated financial intermediaries do, originating more and cheaper loans to these firms. We establish these results using supervisory data on firmbank relationships, syndicated lending data for banks and nonbanks, and an empirical setting with quasirandom shocks to firm profitability. Although credit migrates from banks to nonbanks, zombie firms file for bankruptcy at an elevated rate, suggesting that nonbanks' zombie lending does not enhance the survival rate of distressed and unprofitable firms.
Keywords: G21; G32; G33; 330; zombie lending; zombie firms; banks; nonbanks